The role of perceived legitimacy in understanding traffic rule compliance: A scoping review. (September 2021) - Varet, Florent; Granié, Marie-Axelle; Carnis, Laurent; Martinez, Frédéric; Pelé, Marie; Piermattéo, Anthony
Highlights: Perceived legitimacy of traffic rules is an important determinant of compliance. Its main definitions, measurement, determinants and outcomes were identified. Its definitions and measurements present heterogeneity and validity issues. Insights for the development of a multidimensional model are proposed. Most identified studies are cross-sectional and rely on self-declared behaviours. Abstract: Background: Perceived legitimacy associated with rules and authorities is an important element for understanding and encouraging compliance with rules in the field of road safety, often more so than with a deterrence approach. Despite a growing interest in legitimacy in recent decades and in the psychological field in particular, its definitions and measurements appear to be heterogeneous, subject to debate and in need of a common theoretical framework. Therefore, one can expect these limitations to also concern the definitions and measurements of legitimacy in the field of road safety. However, no literature review related to this issue is currently available. This contribution therefore aims to fill this void by proposing a scoping review investigating, in the field of road safety, how legitimacy is defined, measured, related to compliance and what are its main determinants. Methods: A scoping review was conducted, based on research literature from eight databases and concerned with the perceived legitimacy of traffic rules or traffic enforcement and rule compliance or traffic violations. Twenty-six publications meeting inclusion criteria were retained. The characteristics and content of publications were analyzed to identify the relevant elements related to our research questions. Results and conclusion: The main results revealed that perceived legitimacy in the field of road safety can be related to different objects (i.e., traffic rules, traffic violations, traffic enforcement, institutions) that should be better delineated and differentiated in future research. While perceived legitimacy is generally associated with compliance with traffic rules, its theoretical definitions and measures in the field of road safety are heterogeneous and present validity issues which limit the comparability of studies and so the accumulation of knowledge for both theoretical research and road safety applications. No empirical study investigating the outcomes of perceived legitimacy beyond compliance was identified. Few empirical studies have investigated the determinants of perceived legitimacy. Most identified empirical studies were cross-sectional, which is a limitation to establishing causality in investigated relationships. Theoretical implications and research perspectives to improve studies on legitimacy in the field of road safety and develop a multidimensional model of the perceived legitimacy of traffic rules are therefore proposed and discussed.